Keyworker mediated enhancement of physical health in patients with first episode psychosis: A feasibility/acceptability study. (30th October 2021) - Broughan, John; McCombe, Geoff; Lim, Jayleigh; O'Keeffe, Donal; Brown, Katherine; Clarke, Mary; Corcoran, Ciarán; Hanlon, David; Kelly, Ned; Lyne, John; McGorry, Patrick; O' Brien, Sinéad; et al.
Abstract: Aim: Early intervention for people experiencing first episode psychosis is a priority, and keyworkers are vital to such services. However, keyworkers' roles in addressing first episode psychosis patients' physical health are under researched. This study addresses this knowledge gap by evaluating a keyworker‐mediated intervention promoting physical health among first episode psychosis patients. Methods: The study was informed by the Medical Research Council's Framework for Complex Interventions to Improve Health. First episode psychosis participants were recruited from three Irish mental health services. The intervention was evaluated in terms of its feasibility/acceptability. Results: Feasibility outcomes were mixed (recruitment rate = 24/68 [35.3%]; retention rate = 18/24 [75%]). The baseline sample was predominantly male (M:F ratio = 13:6; Med age = 25 y; IQR = 23‐42 y). Common health issues among participants included overweightness/obesity (n = 11) and substance use (smoking/alcohol consumption [n = 19]). Participants' initial health priorities included exercising more (n = 10), improving diet (n = 6), weight loss (n = 7) and using various health/healthcare services. The intervention's acceptability was evidenced by the appreciation participants had for physical health keyworkers' support, as well as the healthy lifestyle, which the intervention promoted. Acceptability was somewhat compromised by a low‐recruitment rate, variable linkages between keyworkers and general practitioners (GPs) and COVID‐19 restrictions. Conclusions: Physical health‐oriented keyworker interventions for first episode psychosis patients show promise and further evaluation of such initiatives is warranted. Future interventions should be mindful of participant recruitment challenges, strategies to enhance relationships between keyworkers and GPs, and if necessary, they should mitigate COVID‐19 restrictions' impacts on care.